Desenvolvimento de compósito de policloreto de vinila (PVC) reforçado com fibra de vidro - Araújo, Daniela Gomes de (Universidade Federal de São Carlos, 2012)
This work was focused on the evaluation of the interface between short fiber glass and polymeric matrix of the PVC composites using four different sizings as fiber superficial treatment. The interface analysis was done through mechanical properties study and scanning electron microscospy (SEM), while compared with unreinforced PVC compound. The PVC formulation was mixed in a mixer and, after that, 10% in weight of 4 mm fiber glass was introduced and mixed manually in the compound. The initial plan was prepare plates of the glass reinforced PVC samples through a single screw extruder to get parts for analysis, however, this process was not enough to homogenize the fibers in the PVC matrix. Due to it, a new plan was defined and the plates were milled, it was processed in a double screw extruder to obtain pallets and parts for analysis were molded through injection molding. The results attained suggested that, all superficial treatments evaluated showed satisfactory adhesion between the fiber glass and PVC matrix, besides showing an excessive fiber length reduction due to the composite processing with consequent reduction of fiber performance.
Development of glass fiber reinforced PVC composite
Keywords: Engenharia de materiais; PVC; Fibra de vidro; Compósitos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA